METHODOLOGICAL PROPOSAL FOR THE MEASUREMENT OF NATIONAL SECURITY - Zavaleta Ramos, Humberto (2021)
Security is both an individual and collective need, becoming one of the main concerns of the States, at the international level, leading them to establish public policies that guarantee National Security. Based on its importance, this research aimed, in the first instance, to demonstrate the correlational existence between compliance with the objectives of the National Security policy and the level of National Security, in order to develop a methodological proposal for measuring the National Security, the latter being the main objective of the investigation. The research was descriptive-correlational type; the quantitative approach, and the non-experimental and cross-sectional design. The population was made up of experts on the subject of National Security and Defense; while the sample consisted of 30 experts in National Security and Defense. Regarding the data collection techniques and instruments, these were the interview and the questionnaire, respectively. It should be noted that for the hypothesis test the SPPS version 24 software was used, choosing the Spearman Rho statistical test; Based on the results obtained, the methodological proposal for measuring National Security was elaborated. It was found that compliance with the objectives of the National Security and Defense Policy are directly related to the level of National Security. Therefore, it was concluded that the measurement proposal should be carried out in two moments: first, the development of the appropriate indicators, and then measure National Security in Phase 4 of the Strategic Planning for Continuous Improvement.